1979
DOI: 10.1002/macp.1979.021800911
|View full text |Cite
|
Sign up to set email alerts
|

Association of block copolymers in selective solvents 2. Viscosity, diffusion and light‐scattering measurements on hydrogenated poly(styrene‐isoprene) in trans‐decalin/decane mixtures

Abstract: The association of a hydrogenated poly(styrene-isoprene) block copolymer has been studied in mixtures of a selective (decane) and a non-selective solvent (trans-decalin). Viscosity, diffusion and light-scattering studies were made within the temperature range of 25-100°C. Relatively small, compact micelles with a rather monodisperse distribution are found at low temperatures and high decane concentrations; very large, polydisperse associates are formed at intermediate decane concentrations and also at increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

1983
1983
1998
1998

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 4 publications
0
11
0
Order By: Relevance
“…Optically clean solutions of small macromolecular particles should have a Z value near unity . Several research groups have investigated the asymmetry factor Z as a function of temperature near the onset of the micellization and found that there is a peak that in some cases appears at the same temperature as the peak in the scattering curve (see Figure ). ,, We also observed a maximum in the plot of Z as a function of temperature. This is shown in Figure for the 0.77 and 0.97 wt % fractionated block copolymer samples in DMF containing 4.50 wt % water.…”
Section: Resultsmentioning
confidence: 60%
“…Optically clean solutions of small macromolecular particles should have a Z value near unity . Several research groups have investigated the asymmetry factor Z as a function of temperature near the onset of the micellization and found that there is a peak that in some cases appears at the same temperature as the peak in the scattering curve (see Figure ). ,, We also observed a maximum in the plot of Z as a function of temperature. This is shown in Figure for the 0.77 and 0.97 wt % fractionated block copolymer samples in DMF containing 4.50 wt % water.…”
Section: Resultsmentioning
confidence: 60%
“…In addition, spherical micelles have been observed in many studies of block copolymers in solution where the solvent preferentially solvates one of the blocks. Although there are several reports in the literature of the formation of cylindrical micelles from block copolymers, such systems are uncommon, and understanding of them remains poor. Many of the early reports of nonspherical micelles were complicated by the so-called anomalous effect in which certain block copolymer solutions would exhibit a milky opalescence with a large angular dissymmetry at concentrations or temperatures near the onset of micellization …”
Section: Introductionmentioning
confidence: 99%
“…On the other hand it is a well-established fact that block copolymers consisting of nonpolar dissimilar blocks can form micelles in selective solvents, i.e. solvents that are good for one block but are precipitants for the other.…”
Section: Introductionmentioning
confidence: 99%